2020
DOI: 10.1124/dmd.120.000096
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of α,β-Unsaturated Carboxylic Acids Through Acyl Glucuronidation

Abstract: Following oral administration of [ 14 C]GDC-0810, an α,β-unsaturated carboxylic acid, to monkeys, unchanged parent and its acyl glucuronide metabolite, M6, were the major circulating drug-related components. In addition, greater than 50% of circulating radioactivity in plasma was found to be non-extractable 12 hours post-dose, suggesting possible covalent binding to plasma proteins. In the same study, one of the minor metabolites was a cysteine conjugate of M6 (M11) that was detected in plasma and excreta (uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Discrete diglucuronides on two different types of functional groups were rare (Burkon 2008 and Springer 2019) (King 1991). (Mulder 2020) where it was called M1. Following a single oral dose of [ 14 C]GDC-0810 in rats, M6…”
Section: Discussionmentioning
confidence: 99%
“…Discrete diglucuronides on two different types of functional groups were rare (Burkon 2008 and Springer 2019) (King 1991). (Mulder 2020) where it was called M1. Following a single oral dose of [ 14 C]GDC-0810 in rats, M6…”
Section: Discussionmentioning
confidence: 99%
“…117,118 In contrast, M2 and M4 were not detected in the rat and monkey mass balance study following oral administration of [ 14 C]GDC-0810. 119 Several in vitro studies with incubations of [ 14 C]GDC-0810 in human liver and intestinal microsomes and hepatocytes were conducted to further understand the formation of M2. The results showed that minor amounts of M2 were only detected in liver microsomes and hepatocytes.…”
Section: Unexpected Major Metabolites In Circulationmentioning
confidence: 99%
“…This is another example of drug bioactivation through a phase II conjugation reaction. Other examples of conjugation leading to bioactivation include the carboxylic glucuronidation of GDC-0810 activating a,b-double bond for nucleophilic conjugate addition (Mulder et al 2020), and the carboxylic glucuronidation of gemfibrozil and clopidogrel leading to bioactivation via CYP2C8 (Ma et al 2017). Gan et al summarized the bioactivation mechanisms that were catalyzed by non-P450 enzymes (Popovic et al 2010;Gan et al 2016).…”
Section: Commentarymentioning
confidence: 99%